Analisis likuiditas dan ukuran perusahaan terhadap profitabilitas - Yulianto, Eka; Apandi, Aden; Noersanti, Lina; Ardheta, Preztika Ayu; Maliki, Fanisyah (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This research aims to determine and analyze the effect of liquidity and company size on profitability. The method used in this research is quantitative causality research, namely research to describe the company's condition, which is carried out with analysis based on the data obtained. The population in this research are companies operating in the food and beverage consumer goods sector listed on the Indonesia Stock Exchange for the 2017-2021 period, totaling 20 companies. The companies used as samples have financial information from the research. Based on the sample criteria, 20 companies operating in the consumer goods sector that have gone public are worthy of being used as samples in this research. Data analysis techniques using Eviews 12.0 software to process variable data in this research are descriptive statistics, classical assumption tests, panel data regression model tests, panel data regression model selection tests, hypothesis tests, and coefficient of determination tests. The results of this research show that liquidity has an effect on profitability, and company size has no effect on profitability.This research aims to determine and analyze the effect of liquidity and company size on profitability. The method used in this research is quantitative causality research, namely research to describe the company's condition, which is carried out with analysis based on the data obtained. The population in this research are companies operating in the food and beverage consumer goods sector listed on the Indonesia Stock Exchange for the 2017-2021 period, totaling 20 companies. The companies used as samples have financial information from the research. Based on the sample criteria, 20 companies operating in the consumer goods sector that have gone public are worthy of being used as samples in this research. Data analysis techniques using Eviews 12.0 software to process variable data in this research are descriptive statistics, classical assumption tests, panel data regression model tests, panel data regression model selection tests, hypothesis tests, and coefficient of determination tests. The results of this research show that liquidity has an effect on profitability, and company size has no effect on profitability.